The Relationship Between Training Intensity, Rest Patterns, and Nutritional Intake with Physical Fatigue of Athletes at BPPLOP Central Java. - ardhi_prabowo suro the family; Donny Wira Yudha Kusuma (Journal of Physical Education and Sports, 2026)
Physical fatigue is a major challenge for martial arts athletes, especially those in the Central Java BPPLOP (Center for Education and Training of Student Athletes). Factors such as training intensity, rest patterns, and nutritional intake significantly affect fatigue levels. This study aims to analyze the effects of training intensity, rest patterns, and nutritional intake on physical fatigue in martial arts athletes, including pencak silat, wrestling, wushu, boxing, fencing, taekwondo, karate, and judo, at BPPLOP Central Java. This quantitative research employed a survey method. The sample consisted of martial arts athletes at BPPLOP Central Java. Data were collected using questionnaires measuring training intensity, rest patterns, nutritional intake, and physical fatigue. Data were analyzed using multiple linear regression. The findings indicate that rest patterns and nutritional intake significantly affect physical fatigue, while training intensity does not show a significant individual effect. However, all three variables jointly have a significant influence on athletes' physical fatigue. Effective management of physical fatigue in martial arts athletes requires a holistic approach, incorporating balanced training intensity, improved rest patterns, and adequate nutritional intake to maintain optimal performance and reduce injury risks.       https://drive.google.com/drive/folders/1HiuufJ6aY7Fv5EYZL9mjxUaI25u_CPHk?usp=drive_link